Humor gráfico na ditadura civil-militar brasileira (1964-1985) : as charges políticas de Orlando Mattos, Ziraldo e Angeli - Ferreira, Fábio Donato (2023)
This research aims to analyze the trajectory of three cartoonists in the period of the Brazilian civil-military dictatorship (1964-1985), through the periodicals Folha de S.Paulo and Jornal do Brasil. If you look for elements of graphic humor that corroborate or that go against the laws and impositions of the government, thus bringing the cartoon as the historical source of a certain moment, and with the pertinent analysis of the entire period of the military government, we can perceive the game of forces of the press with the authoritarianism instituted in the country. The materials published by Orlando Mattos, Ziraldo and Angeli, in these journals, which circulated in the states of Rio de Janeiro and São Paulo, were surveyed, cataloged and analysed, had a large national coverage, in addition to greater circulation.